2016
DOI: 10.1155/2016/5671507
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Molecular Imprinting Polymer Microspheres of Piperine: Extraction of Piperine from Spiked Urine

Abstract: Molecularly imprinted polymer (MIP) microspheres for Piperine were synthesized by precipitation polymerization with a noncovalent approach. In this research Piperine was used as a template, acrylic acid as a functional monomer, ethylene glycol dimethacrylate as a cross-linker, and 2,2′-azobisisobutyronitrile (AIBN) as an initiator and acetonitrile as a solvent. The imprinted and nonimprinted polymer particles were characterized by using Fourier transform infrared spectroscopy (FT-IR) and Scanning Electron Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…9a and b, present the surface morphology of CR1-MIP particles The micrographs clearly revealed the surface with a porous texture having very tiny and homogeneous spherical particles that have been developed with a narrow size distribution in the range of micrometers ~ 0.07 µm. Uniformity in size and shape was owed to non-covalent precipitation polymerization method [41][42][43][44]. The uniformly sized MIP have advantages of possessing 'large surface area, monodispersed, colloidal stability' as compared to the irregularly shaped MIP particles.…”
Section: Tga Analysis Of Cr1-mipmentioning
confidence: 99%
“…9a and b, present the surface morphology of CR1-MIP particles The micrographs clearly revealed the surface with a porous texture having very tiny and homogeneous spherical particles that have been developed with a narrow size distribution in the range of micrometers ~ 0.07 µm. Uniformity in size and shape was owed to non-covalent precipitation polymerization method [41][42][43][44]. The uniformly sized MIP have advantages of possessing 'large surface area, monodispersed, colloidal stability' as compared to the irregularly shaped MIP particles.…”
Section: Tga Analysis Of Cr1-mipmentioning
confidence: 99%
“…Recent studies showed that the preparation of MIMs using precipitation polymerisation has successfully led to different templates [ 55 , 56 , 58 , 59 , 60 , 61 , 90 , 91 , 92 , 93 , 94 ] and sensors [ 107 ], and extracted various analytes from natural ingredients [ 95 , 111 , 112 , 113 ], biological samples [ 62 , 63 , 64 , 65 , 108 ], foods [ 96 , 97 , 109 , 114 , 115 ] and wastewater [ 98 , 99 ]. As an easy, simple and commonly used strategy for producing MIMs, precipitation polymerisation has great potential for developing advanced strategies in combination with other approaches (molecularly imprinted solid phase extraction (MISPE), biochemical sensors, high performance liquid chromatography (HPLC), etc.)…”
Section: Preparation Of Molecularly Imprinted Microspheresmentioning
confidence: 99%
“…All the polymer particles were spherical in shape and the size is in the micro range [NIP (0.68 µm) and MIP (1.22 µm)]. This is due to the advantage of precipitation polymerization method [16][17][18] and the favorable uniform size distribution between the interaction of monomer and template. The uniform shape and size of polymer particles may be due to the solvent (acetonitrile).…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 99%